Pengembangan Motif Batik Tulis Kembang Randu Sebagai Upaya Pelestarian Kearifan Lokal Desa Petekeyan - Muhammad Iqbal Maulana; Fata Zumala; Zul Faizah; Dicky Wahyu Febriansyah; Abdul Ghofur; Aliffia Fajar Agustin; Ikhsan; Henna Haati Auniah; Rosi Choirunnisa; Lina Hikmawati; Luky Mudiarti (Khaira Ummah, 2022)
Batik is an Indonesian cultural heritage that has been designated by UNESCO. This makes each region expected to be able to have batik in accordance with the local wisdom of their respective regions. Petekeyan Village actually already has a batik motif but with a very simple motif design. Therefore, it is necessary to develop batik motifs with the characteristics of Petekeyan village based on local wealth that can be recognized by the wider community. This service is carried out with the aim of developing written batik flower randu with an orientation to local wisdom that is able to become a characteristic of Petekeyan village batik. The method used in this service is Focus Group Discussion with several community leaders regarding history, culture and local wisdom involving members of the youth organization, and training by bringing in presenters by demonstrating how to make batik up to the coloring stage to partners in order to increase their knowledge about batik. The results of this service are: (1). Assist in the procurement of tools and materials in the batik coloring process, (2). The development of the Petekeyan flower motif batik motif design based on local wisdom in Petekeyan village, namely the randu flower motif and the peacock motif which became the icon of Petekeyan village, (3). Conducting training with the aim of being able to recruit members, and (4). Introducing the typical batik products of Petekeyan village to the community.